2013
DOI: 10.1002/cncr.28320
|View full text |Cite
|
Sign up to set email alerts
|

The cumulative risk of false‐positive results in the Norwegian Breast Cancer Screening Program: Updated results

Abstract: BACKGROUND: Some false-positive results are inevitable in mammographic screening, but the impact of false-positive findings on the program and the participants is a disadvantage of screening. The objective of the current study was to estimate the cumulative risk of a false-positive result over 10 biennial screening examinations and the cumulative risk of undergoing an invasive procedure with a benign outcome in women screened between the ages of 50 years to 69 years. METHODS: A retrospective cohort study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
5
18
0
1
Order By: Relevance
“…Similar to prior studies comparing screening in the US and Europe, we found substantially higher risks of false-positive recall in the BCSC compared to Nijmegen, while risks of screen-detected cancer were similar (12, 20, 24). Possible explanations for these differences include the opportunistic nature of screening in the US, as compared to organized population-based screening in Europe; differences in the medico-legal context; and differences in interpretive volumes required for radiologist accreditation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to prior studies comparing screening in the US and Europe, we found substantially higher risks of false-positive recall in the BCSC compared to Nijmegen, while risks of screen-detected cancer were similar (12, 20, 24). Possible explanations for these differences include the opportunistic nature of screening in the US, as compared to organized population-based screening in Europe; differences in the medico-legal context; and differences in interpretive volumes required for radiologist accreditation.…”
Section: Discussionsupporting
confidence: 87%
“…A number of prior studies have estimated the cumulative risk of a false-positive screening mammography result using data from European population-based screening programs (7-9, 12, 20). Some of these studies have used discrete-time survival estimates (7, 12, 20) while others have used simpler approximations that assume independence of risk across screening rounds (8, 9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the individual level, the risk of a false-positive result varies with mammographic density [109], which is associated with hormone therapy and other breast cancer risk factors [154]. At a population level, the risk of a false-positive result will depend on the distribution of such factors in the population and on technical and organizational aspects of the screening program that affects sensitivity (digital versus film mammography, double versus single reading, experience/reading volume of the radiologist, acceptance of mistakes and trends in medical ethics -i.e.…”
Section: Characterization Strengths and Limitationsmentioning
confidence: 99%
“…Encore de nos jours, de nombreux tests utilisés pour poser un diagnostic de cancer comportent un risque de faux positif. Le risque est particulièrement élevé lors du dépistage de cancers précoces asymptomatiques (Crothers et al, 2014;Roman et al, 2013). Si, à la suite de ce mauvais diagnostic, le patient se rend à Lourdes ou prie un saint d'intercéder auprès de Dieu pour que celui-ci le guérisse, il sera facile de conclure au miracle.…”
Section: Hypothèses Alternativesunclassified